From pin money to side hustle: Rural and regional women's side businesses in Australia 1900–2023 - Prowse, Louise (Asia‐Pacific Economic History Review, 2024)
Abstract In the last 15?years, mainstream use of the term ?side hustle? has boomed. But the act of having a side hustle is not new; the term's novelty obscures a long-established pattern of ?sideline earning? by Australian rural women, and indeed around the world. Through the lens of environmental, labour and gender history, and using interviews, digital media, diaries, court records, newspaper and magazine articles and other archival records, this research explores how Australian rural women have engaged in and relied on the practice of sideline earning as an economic necessity, long before it entered the mainstream economy and consciousness.
Keywords: Australian rural business history; rural women; side-business; side-hustle